Indonesian Takfiri Movement on Online Media in Umberto Eco's Semiotic Perspective - Aniek Nurhayati; Dwi Astiti Hadiska Putri; Andin Desnafitri (Islamica: Jurnal Studi Keislaman, 2021)
In the era of online media, the Takfiri movement uses websites and social media to propagate its religious understanding. In Indonesia, they also do the same. Through a semiotic perspective, this paper seeks to question how communication and interpretation are carried out by Takfiri groups in producing signs, and how they express signs in online media. The relevance of Umberto Eco’s semiotics is due to its communicational character, and as a contemporary semiotic philosopher, Eco has reminded of how sign production is happening in the era of internet technology. With narrative and semiotic analysis methods, this paper draws data from online media in the form of websites and social media such as Twitter, Instagram and Facebook. The analysis shows that Takfiri content in online media, which creates radical attitudes in some circles of society, has been captured without a meaningful process, so there is no critical thinking process. The propaganda of Takfiri is expressed in the very well-known sentence, al-walā’ wa al-barā’, namely love and loyalty to believers and hate, and hostility to unbelievers, and it is a sign that Takfirism is an ideology whose followers are ready to commit violence in the name of religion.